2017
DOI: 10.1177/0042098017712680
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transit, transit-oriented development, and the contextual sensitivity of land value uplift in Toronto

Abstract: Rapid transit projects that increase accessibility should result in a localized land value uplift (LVU) benefit for locations near stations. A rich history of research has tested this hypothesis, generally operationalizing transit accessibility by proxy through distance from a transit station. However, a growing body of research has also demonstrated LVU effects from transit-oriented development (TOD) as individuals sort themselves into locations that best match their preferences and willingness to pay. Consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 35 publications
(47 reference statements)
2
25
0
Order By: Relevance
“…An extensive body of literature has confirmed that TOD-based development plays an important and positive role in urban land markets [19]. The change features within different distances have been discussed [5,6]. Petheram et al [20] reported that, in the Salt Lake City metropolitan area, the minimum market-driven catchment area of a light rail station can extend to 1.25 miles, which is clearly far beyond normal walking distance.…”
Section: Research Related To Catchment Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive body of literature has confirmed that TOD-based development plays an important and positive role in urban land markets [19]. The change features within different distances have been discussed [5,6]. Petheram et al [20] reported that, in the Salt Lake City metropolitan area, the minimum market-driven catchment area of a light rail station can extend to 1.25 miles, which is clearly far beyond normal walking distance.…”
Section: Research Related To Catchment Areasmentioning
confidence: 99%
“…In previous studies, TOD catchment areas (CA) have been discussed mainly by walking distance [1,2], ridership prediction [3,4], and in relation to land value [5,6]. Because of the different understandings and interpretations of the TOD concept, a one-size-fits-all approach is counterproductive [7].…”
Section: Introductionmentioning
confidence: 99%
“…Du and Mulley [29,30] observed various effects (a mix of positive, none, and negative) of transport accessibility on land value from place to place in the United Kingdom. Other studies have shown that the increase of property values does not benefit much from the proximity to public transportation but rather the property's characteristics and its neighborhood features [31][32][33].…”
Section: Introductionmentioning
confidence: 97%
“…Based on the conclusions of the study, the total increase near the transit area was divided into two categories. The first is the effect of a specific TOD station, which increases by 20%, while the second is due to the proximity effect of the property to the transit station with a greater increasing value assuming it is adjacent to the transit station 5) . This study shows that the increases in land differ by the location characteristics, such as inner, outer, and suburban neighborhoods.…”
Section: Introductionmentioning
confidence: 99%